Characterization of the near-surface air temperature dynamics over glaciers using thermal infrared measurements - Mott, Rebecca; Haugeneder, Michael; Stiperski, Ivana; Asemann, Patricia; Reynolds, Dylan; Nicholson, Lindsey (Frontiers in Earth Science, 2025)
Alpine glaciers are undergoing rapid mass loss, primarily driven by rising summer air temperatures. However, the glacier microclimate, especially the role of atmospheric dynamics near the surface and turbulent fluxes, is not adequately understood. This study examines the structure and variability of the glacier boundary layer, focusing on katabatic winds and their modulation by synoptic-scale disturbances. Using a high-resolution thermal infrared (TIR) camera (InfraTec VarioCam HD) directed at synthetic screens, we recorded spatio-temporally resolved air temperature fields within the lowest 4 m above the glacier surface. These measurements were complemented by turbulence data from a 5-m eddy covariance tower, enabling a combined analysis of thermal stratification and turbulent mixing. Our results reveal persistent temperature stratification during katabatic flow, often marked by strong gradients and localized zones of high temperature variance associated with the katabatic jet. These layers are intermittently disrupted by cross-glacier or synoptic-scale flows, enhancing turbulent mixing and advecting warm air toward the surface. The height of maximum temperature variance frequently coincided with the approximate jet height estimated from turbulence measurements, suggesting a link between glacier wind dynamics and thermal structure. However, this relationship weakens under fluctuating flow regimes, highlighting the complexity of glacier boundary layer processes and suggesting that stratification and mixing are highly sensitive to the vertical structure of glacier winds. The use of TIR imaging offers unique insights into the fine-scale temperature dynamics of glacier boundary layers, overcoming limitations of discrete-level turbulence sensors and enabling continuous spatial assessment of flow features. Our findings underscore the importance of shallow katabatic winds in enhancing near-surface mixing, with implications for the surface energy balance and, ultimately, glacier melt. Future research should combine this approach with advanced heat budget models and adapted methods such as the WEIRD technique to further unravel the complex coupling between glacier winds, atmospheric turbulence, and climate sensitivity of mountain glaciers.